2023
DOI: 10.3390/coatings13030644
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Perovskite Solar Cells: Status and Future

Abstract: The power conversion efficiency (PCE) of perovskite solar cells (PSCs) has seen effective performance upgrades, showing remarkable academic research and commercial application value. Compared with commercial silicon cells, the PCE gap is narrowing. However, the stability, cost, and large-scale production are still far behind. For scale-up preparing high-efficiency and stable PSCs, there is a variety of related research from each functional layer of perovskite solar cells. This review systematically summarizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 224 publications
0
5
0
Order By: Relevance
“…spiro-OMeTAD, for example, is among the most commonly employed HSLs in conventional-architecture devices. [68,69] However, the p-type dopants necessary to improve the charge transport capacity of the neat material contribute to poor longterm stability. Lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) absorbs ambient moisture, and 4-tert-butylpyridine (TBP) evaporates from the film, leading to the formation of voids and pinholes (Figure 3).…”
Section: Stabilitymentioning
confidence: 99%
“…spiro-OMeTAD, for example, is among the most commonly employed HSLs in conventional-architecture devices. [68,69] However, the p-type dopants necessary to improve the charge transport capacity of the neat material contribute to poor longterm stability. Lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) absorbs ambient moisture, and 4-tert-butylpyridine (TBP) evaporates from the film, leading to the formation of voids and pinholes (Figure 3).…”
Section: Stabilitymentioning
confidence: 99%
“…Thus, dissolving the lead precursor salt into a solvent with a low boiling point, such as methanol, promotes faster evaporation of the solvent from the film and improves the film quality. Replacing commonly used toxic solvents such as N , N- dimethylformamide (DMF) with methanol has an additional positive impact on reducing the environmental burden of the process . Acetic acid (HAc), as an additive in the lead acetate solution, promotes better solubility of the metal salt at a lower pH .…”
Section: Introductionmentioning
confidence: 99%
“…Replacing commonly used toxic solvents such as N , N- dimethylformamide (DMF) with methanol has an additional positive impact on reducing the environmental burden of the process. 31 Acetic acid (HAc), as an additive in the lead acetate solution, promotes better solubility of the metal salt at a lower pH. 32 It has also been indicated that the presence of acetates in the perovskite precursor solution can improve the performance of the solar cell by an increase of the short-circuit current, 33 making the precursor solution an optimal choice for a two-step deposition using dip coating in both deposition stages.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen significant advancements in solar power, notably in the field of photovoltaic (PV) technology, in which solar energy could be integrated into energy production along with other sources such as coal, biomass, wind, and geothermal [72]- [74]. The manufacture of perovskite solar cells has the promise of increased efficiency as well as decreased manufacturing costs, which has the possibility of completely transforming the market [75]- [78]. Building-integrated photovoltaics, which is an expansion of solar technology that incorporates solar energy tracking systems and the incorporation of solar activity into construction supplies, has increased the usefulness of solar technology while also improving its aesthetics [79], [80].…”
Section: Introductionmentioning
confidence: 99%